2007
DOI: 10.1002/ar.20597
|View full text |Cite
|
Sign up to set email alerts
|

Claudin‐7 Expressed on Lateral Membrane of Rat Epididymal Epithelium does not Form Aberrant Tight Junction Strands

Abstract: Claudins are integral membrane proteins at tight junctions (TJs) and form TJ strands. In the present study, we found that claudin-7 was localized along the entire lateral membranes of epididymal epithelium, including the apical junctional region throughout the epididymis, but claudin-8 was restricted to the apical junctional region. This finding raises the possibility that aberrant TJ strands may be formed on lateral membranes. Thus, we focused on examining whether TJ strands exist on lateral membranes of epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…2E). Although Claudin proteins are components of tight junctions and typically localize to the subapical region (Furuse et al, 1998), studies have shown that several members of this protein family also localize to lateral membranes during morphogenesis (Gregory et al, 2001;Inai et al, 2007;Westmoreland et al, 2012), including the closely related zebrafish claudin Cldn15lb (Cheung et al, 2012). To determine whether Cldn15la-GFP lateral membrane localization represented the endogenous protein localization we generated an antibody against the C-terminus of Cldn15la.…”
Section: Rapid Lumen Expansion and Fusion During Tubulogenesismentioning
confidence: 99%
“…2E). Although Claudin proteins are components of tight junctions and typically localize to the subapical region (Furuse et al, 1998), studies have shown that several members of this protein family also localize to lateral membranes during morphogenesis (Gregory et al, 2001;Inai et al, 2007;Westmoreland et al, 2012), including the closely related zebrafish claudin Cldn15lb (Cheung et al, 2012). To determine whether Cldn15la-GFP lateral membrane localization represented the endogenous protein localization we generated an antibody against the C-terminus of Cldn15la.…”
Section: Rapid Lumen Expansion and Fusion During Tubulogenesismentioning
confidence: 99%
“…A striking example is claudin-7, which is predominantly basolateral in the connecting tubule and collecting duct (68), as it is in airway, intestinal, and epididymal epithelia (23,42,51). At least in the epididymis it is not polymerized into strands (51).…”
Section: Expression and Localization Of Claudins In The Kidneymentioning
confidence: 99%
“…It has previously been reported that the rat and human epididymis contain a large number of CLDNs [24][25][26][27][28]. The combination of CLDNs determines the selective permeability of the barrier [29].…”
Section: Introductionmentioning
confidence: 99%